STUDYING OF SAFETY CLIMATE ASSESSMENT: A CASE STUDY AT STEEL INDUSTRY - Hassan DARVISH; Mehdi ROOSTAEI; Saeed AZIZI (Management & Marketing)
Evolution of safety climate used as a practical means has determined and assessed potential problems relevant to safety issues in an organization and can be used in individuals’ performance and work efficiency and decreasing rate of incidents ;as well as; guidance to provide safety organization policy and comparison of safety performance in different organizations. The study wants to determine and prepare safety climate profile and application of its results in improving safety situation. In this study, applied tools presented by Loughborough University are used to evaluate safety climate in one of steel industries and data is collected through questionnaire, group discussions or purposeful interviews and observations, and safety climate score was obtained in 17 scopes. Calculating the score of each safety climate domain and preparing the profile indicated there is the average rate (4.89 2) in the safety climate of the industry.